Using virtual reality in large-scale industry project - Woksepp, Stefan; Olofsson, Thomas (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2006)
The Swedish state-owned mining company LKAB has recently initiated the process of building a new pelletizing plant (MK3) in Malmberget, northern Sweden. The total expenditure will amount to €280 million and the new plant is expected to be operational around the turn of the year 2006-2007. Contractors are expected to employ a workforce of about 250 in connection with the construction of the plant, while some 150 consultants and engineers are engaged in the design phase. Since time to market is a crucial factor for LKAB, the contractual agreements for cooperation in the project support collaborative working methods such as concurrent engineering, open information flow and introduction of innovations in the design process. The complexity of the project, the number of actors involved and the desire to involve the client and the end-users, such as industrial workers responsible for the future plant operations, in the design work makes Virtual Reality (VR) an excellent enriched source of communications. This paper describes findings from a case study that sought to explore and document the practical work and experiences achieved, including some good examples, from using VR in the design and planning process. Validerad; 2006; 20061221 (ysko)